De novo transcriptome profiling reveals the bioeffect of the clam (Cyclina sinensis) to graded extremely low-frequency electromagnetic fields (ELF-EMF, 50 Hz) exposure - Mingming Zhang; Yuqing Fan; Mingfeng Zhu; Shouhai Liu; Hu Zhang; Chaojun Gu; Zhenyu Wang; Boping Yang; Guo Qiao (Environmental Pollution, 2026)

A novel non-nad-based PARP1 inhibitor, Japoflavone B, triggered Caspase-3/GSDME-mediated pyroptosis through ROS/p38/p53 pathway in NSCLC - Haoqiang Wan; Jipeng Wei; Yang Wang; Lanlan Ge; Qiaoqiao Hu; Yangfang Li; Boping Zhou; Xiaobin Zeng (Chemico-Biological Interactions, 2025)

Whole genome evaluation analysis and preliminary Assembly of Oratosquilla oratoria (Stomatopoda: Squillidae) - Xiaoli Sun; Gang Wang; Jie Yang; Wei Yu; Jiayue Xu; Boping Tang; Ge Ding; Daizhen Zhang (Molecular Biology Reports, 2023)

The Effect of Food Deprivation on Foraging Behavior and Digestive and Metabolic Capacities of the Chinese Mitten Crab, Eriocheir sinensis - Qiaolin Long; Jian Liu; Yunfei Sun; Zhigang Yang; Boping Tang; Yongxu Cheng (Fishes, 2023)
Food deprivation is a common stress in crustaceans that can affect their behavior and physiology. In this study, a video recording analysis system was used to compare the predation rate and behavior of the Chinese mitten crab, Eriocheir sinensis, foraging on the freshwater snail, Bellamya quadrata, under different degrees of food deprivation. The activities of lactate dehydrogenase, α-amylase, pepsin, and lipase in the hepatopancreas of crabs were determined after food deprivation for 0, 3, 9, and 15 days. The results showed that the predation and encounter rates of E. sinensis increased and then decreased with an increase in food deprivation time. The proportion of stationary time of E. sinensis initially decreased and then increased, whereas the proportion of searching and handling time increased initially and then decreased. There was a significant difference in the probability of capture upon encountering; however, food deprivation did not significantly affect the probability of consumption upon capture. Under food deprivation, the proportion of E. sinensis crushing tactics after nine-day food deprivation was significantly lower than that in the first nine days. Lactate dehydrogenase activity in the E. sinensis hepatopancreas after food deprivation was significantly higher than that in those not subjected to food deprivation, and the activities of α-amylase and pepsin in the hepatopancreas were consistent with the predation rate trend, showing an initial increase followed by a decrease. In conclusion, different degrees of food deprivation significantly affected the predation cycle of E. sinensis on B. quadrata. These results lay a solid foundation for further studies on the foraging behavioral ecology of E. sinensis and provide important information for improving E. sinensis production.

Downregulation of Circ-CEP128 Enhances the Paclitaxel Sensitivity of Cervical Cancer Through Regulating miR-432-5p/MCL1 - Ying Zhao; Yi Lan; Yugang Chi; Boping Yang; Chunyan Ren (Biochemical Genetics, 2022)

Comprehensive Utilization of Land Resources for Photovoltaic Power Generation to Culture Chinese Mitten Crab (Eriocheir sinensis): Growth Performance, Nutritional Composition and Tissue Color - Yangyang Pang; Chao Niu; Lifeng Wu; Yameng Song; Xiaozhe Song; Ao-ya Shi; Xingliang Shi; Zong-wen Wu; Boping Tang; Xiaozhen Yang; Yongxu Cheng (Fishes, 2022)
The assertive growth of photovoltaics (PV) will occupy a lot of land resources. There is also a needed land resource to expand the culturing area of Eriocheir sinensis. The aquavoltaic systems offer a potential solution to integrate PV power and E. sinensis culturing. In this study, we cultured E. sinensis in an area of PV panels (PV group) and an area with no PV panels (control group), respectively. The results showed that the weight gain rate, body length, body width, and meat yield of male crabs in the PV group significantly increases. In addition, the moisture of muscles, hepatopancreas, and testes in the PV group has significantly increased, and the total lipids of the hepatopancreas and muscles in the PV group were significantly decreased. Moreover, the PV panels affected the content of eight amino acids in different tissues, including Met, Arg, Cys, Pro, Gly, Leu, Tyr, and His. In addition, several saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) had been significantly influenced by the PV panels. ∑MUFA, docosahexaenoic acid (DHA), ∑n-3 PUFA, ∑n-6 PUFA, and n-3/n-6 PUFA ratio (p

Exploration of molecular mechanism of intraspecific cross-incompatibility in sweetpotato by transcriptome and metabolome analysis - Yiling Yang; Xiongjian Zhang; Hongda Zou; Jingyi Chen; Zhangying Wang; Zhongxia Luo; Zhufang Yao; Boping Fang; Lifei Huang (Plant Molecular Biology, 2022)
Cross-incompatibility, frequently happening in intraspecific varieties, has seriously restricted sweetpotato breeding. However, the mechanism of sweetpotato intraspecific cross-incompatibility (ICI) remains largely unexplored, especially for molecular mechanism. Treatment by inducible reagent developed by our lab provides a method to generate material for mechanism study, which could promote incompatible pollen germination and tube growth in the ICI group. Based on the differential phenotypes between treated and untreated samples, transcriptome and metabolome were employed to explore the molecular mechanism of sweetpotato ICI in this study, taking varieties ‘Guangshu 146’ and ‘Shangshu 19’, a typical incompatible combination, as materials. The results from transcriptome analysis showed oxidation–reduction, cell wall metabolism, plant–pathogen interaction, and plant hormone signal transduction were the essential pathways for sweetpotato ICI regulation. The differentially expressed genes (DEGs) enriched in these pathways were the important candidate genes to response ICI. Metabolome analysis showed that multiple differential metabolites (DMs) involved oxidation–reduction were identified. The most significant DM identified in comparison between compatible and incompatible samples was vitexin-2-O-glucoside, a flavonoid metabolite. Corresponding to it, cytochrome P450s were the most DEGs identified in oxidation–reduction, which were implicated in flavonoid biosynthesis. It further suggested oxidation–reduction play an important role in sweetpotato ICI regulation. To validate function of oxidation–reduction, reactive oxygen species (ROS) was detected in compatible and incompatible samples. The green fluorescence was observed in incompatible but not in compatible samples. It indicated ROS regulated by oxidation–reduction is important pathway to response sweetpotato ICI. The results in this study would provide valuable insights into molecular mechanisms for sweetpotato ICI.

MiR-122-5p knockdown protects against APAP-mediated liver injury through up-regulating NDRG3 - Zhi Yang; Weigang Wu; Pengcheng Ou; Minna Wu; Furong Zeng; Boping Zhou; Shipin Wu (Molecular and Cellular Biochemistry, 2021)

Mitochondrial OXPHOS genes provides insights into genetics basis of hypoxia adaptation in anchialine cave shrimps - Huayun Guo; Hao Yang; Yitao Tao; Dan Tang; Qiong Wu; Zhengfei Wang; Boping Tang (Genes & Genomics, 2018)